Dynamic modelling of induced draft cooling towers with parallel heat exchangers, pumps and cooling water network. (August 2018) - Viljoen, J.H.; Muller, C.J.; Craig, I.K.
Highlights: First principle dynamic model for the operation of a cooling water network. Models for parallel pumps and heat exchangers and piping in the network. Parameter estimation utilising plant data was performed. Pump rotation speeds and cooling tower fan speeds included as Manipulated Variables. Abstract: In the process industries, cooling capacity is an important enabler for the facility to manufacture on specification product. The cooling water network is an important part of the over-all cooling system of the facility. In this paper a cooling water circuit consisting of 3 cooling towers in parallel, 2 cooling water pumps in parallel, and 11 heat exchangers in parallel, is modelled. The model developed is based on first principles and captures the dynamic, non-linear nature of the plant. The modelled plant is further complicated by continuous, as well as Boolean process variables, giving the model a hybrid nature. Energy consumption is included in the model as it is a very important parameter for plant operation. The model is fitted to real industry data by using a particle swarm optimisation approach. The model is suitable to be used for optimisation and control purposes.